2015
DOI: 10.2215/cjn.06620714
|View full text |Cite
|
Sign up to set email alerts
|

T Cells

Abstract: Traditionally, T cells were CD4 1 helper or CD8 1 cytotoxic T cells, and with antibodies, they were the soldiers of immunity. Now, many functionally distinct subsets of activated CD4 1 and CD8 1 T cells have been described, each with distinct cytokine and transcription factor expression. For CD4 1 T cells, these include Th1 cells expressing the transcription factor T-bet and cytokines IL-2, IFN-g, and TNF-b; Th2 cells expressing GATA-3 and the cytokines IL-4, IL-5, and IL-13; and Th17 cells expressing RORgt an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 166 publications
(118 reference statements)
1
65
0
Order By: Relevance
“…Our findings indicated that Th17/Treg immune responses were indeed imbalanced in such patients, corresponding to data from human [6,28] and experimental models [7] previously reported by other researchers. However, the driving force of Th17/Treg imbalance remains unclear [29].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings indicated that Th17/Treg immune responses were indeed imbalanced in such patients, corresponding to data from human [6,28] and experimental models [7] previously reported by other researchers. However, the driving force of Th17/Treg imbalance remains unclear [29].…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α stimulates IDO independent of IFN-γ 26. In this regard, kidney from Allos showed significant increases in the transcription and translation of the IL-β gene when compared with Autos (figure 4A,B).…”
Section: Resultsmentioning
confidence: 90%
“…Rejection is associated with activation of antigen presenting cells, which stimulate CD4 + lymphocytes, promoting the release of inflammatory cytokines that include IL-1β, TNF-α and IFN-γ, all of which further activate antigen presenting cells and amplify T cell responses 26. TNF-α stimulates IDO independent of IFN-γ 26.…”
Section: Resultsmentioning
confidence: 99%
“…T regs in the middle of innate and adaptive immunity T regs may play a role in MCN based on their plasticity and multi-functional effects [61]. Basically, these cells are connected to innate immunity by means of CD80 and may, in turn, modulate the levels of pro-and anti-inflammatory compounds.…”
Section: Animal Modelsmentioning
confidence: 99%